Use of PKA-mediated phenotypes for genetic and small-molecule screens in Schizosaccharomyces pombe. (20th November 2013) - de Medeiros, Ana Santos; Magee, Alexander; Nelson, Kyle; Friedberg, Liora; Trocka, Karolina; Hoffman, Charles S.
Abstract : PKA (protein kinase A) in the fission yeast Schizosaccharomyces pombe controls transcription of genes involved in metabolism, cell growth and sexual development. In the present review, we discuss phenotypes associated with either high or low PKA activity in the context of how they can be used to carry out genetic or small-molecule screens that affect components of the PKA pathway. Although our recent research has focused on the study of heterologously expressed cyclic nucleotide PDEs (phosphodiesterases), these same methods can be used to target other S. pombe proteins or their functionally equivalent orthologues that act in the PKA pathway.